Clinical Practice Guidelines of the Russian Scientific Liver Society, Russian Gastroenterological Association, Russian Association of Endocrinologists, Russian Association of Gerontologists and Geriatricians and National Society for Preventive Cardiology on Diagnosis and Treatment of Non-Alcoholic Liver Disease - V. T. Ivashkin; M. V. Maevskaya; M. S. Zharkova; Yu. V. Kotovskaya; O. N. Tkacheva; E. A. Troshina; M. V. Shestakova; I. V. Maev; V. V. Breder; N. I. Gheivandova; V. L. Doshchitsin; E. N. Dudinskaya; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: present clinical guidelines, aimed at general practitioners, gastroenterologists, cardiologists, endocrinologists, comprise up-to-date methods of diagnosis and treatment of non-alcoholic fatty liver disease.Key points. Nonalcoholic fatty liver disease, the most wide-spread chronic liver disease, is characterized by accumulation of fat by more than 5 % of hepatocytes and presented by two histological forms: steatosis and nonalcoholic steatohepatitis. Clinical guidelines provide current views on pathogenesis of nonalcoholic fatty liver disease as a multisystem disease, methods of invasive and noninvasive diagnosis of steatosis and liver fibrosis, principles of nondrug treatment and pharmacotherapy of nonalcoholic fatty liver disease and associated conditions. Complications of nonalcoholic fatty liver disease include aggravation of cardiometabolic risks, development of hepatocellular cancer, progression of liver fibrosis to cirrhotic stage.Conclusion. Progression of liver disease can be avoided, cardiometabolic risks can be reduced and patients' prognosis — improved by the timely recognition of diagnosis of nonalcoholic fatty liver disease and associated comorbidities and competent multidisciplinary management of these patients.